1961
DOI: 10.1111/j.1151-2916.1961.tb15379.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐Temperature Mechanical Properties of Ceramic Materials: IV, Sintered Mullite Bodies

Abstract: An attempt was made to sinter relatively pure 3&Oa.2Si02 and 2Alz08 .SiOn compositions to low porosities at 1710' and 1650°C., respectively, using an addition of 1% MgO to each body to facilitate the reaction. The 3 & 0~. 2 S i O~ body sintered to a porosity of 7.1% and was practically all mullite. The 2AlZOs.SiOz body sintered to a porosity of 10.9% and was composed of m a t e and corundum. Strength and elastic modulus measurements were made at several temperatures up to 120O0C., and some observations of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1967
1967
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…5 The data of Wachtman and Lam show a distinct nonlinear softening above 600°C. Fenstermacher and Hummel report data which agree in general form with that of Wachtman and Lam although with much more scatter and lower absolute magnitude of E. 6 Our data support a linear fit within their accuracy, with no significant change in the rate of softening. The value of dG/dT based on the present study falls between that reported by Ledbetter et al (Ϫ3.3 MPa/°C) 10 and that suggested by a linear fit to Wygant's data (ϳϪ30 MPa/°C).…”
Section: (2) High-temperature Elasticitysupporting
confidence: 79%
“…5 The data of Wachtman and Lam show a distinct nonlinear softening above 600°C. Fenstermacher and Hummel report data which agree in general form with that of Wachtman and Lam although with much more scatter and lower absolute magnitude of E. 6 Our data support a linear fit within their accuracy, with no significant change in the rate of softening. The value of dG/dT based on the present study falls between that reported by Ledbetter et al (Ϫ3.3 MPa/°C) 10 and that suggested by a linear fit to Wygant's data (ϳϪ30 MPa/°C).…”
Section: (2) High-temperature Elasticitysupporting
confidence: 79%
“…There are reported experimental data (see Table ) on the elastic stiffness constants of single crystal 2/1 mullite and 2.5/1 mullite . In the 2/1 mullite, the reported values for C 11 , C 33 , C 12 , and C 23 from the two sets of measurements are somewhat different.…”
Section: Mechanical Properties Of the Mullite Phasesmentioning
confidence: 99%
“…Because of its wide range of applications, mullites have received considerable attention over the years . A large number of works have covered processing, structure determination, characterization, thermodynamics, thermal, mechanical, and optical properties . Besides the popular monolithic use of mullites, mullite coatings, fibers, and matrix composites are also becoming increasingly popular in modern technology .…”
Section: Introductionmentioning
confidence: 99%
“…Close to the orthorhombic system, it has high melting point (1870°C), good high-temperature mechanical and thermal performances. 15 The mullite product with mullite as the main crystalline phase has high structural strength of high temperature, low creep rate of high temperature, and good chemical erosion resistance. Compared with aluminum silicate with corundum as the main crystalline phase, it has small coefficient of thermal expansion and better stability of thermal shock resistance.…”
Section: Introductionmentioning
confidence: 99%